Analisis Pengendalian Sektor Pariwisata Melalui Tourism Safe Corridor Di Asean Pada Masa Covid-19 - Hardi Alunaza; Safira Christiani; Fera Eliati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
In 2019 the world began to face a situation that had never happened before in the world, where in 2019 many countries in the world were affected by the outbreak, namely Covid-19 which created many socio-economic challenges that must be overcome. The purpose of this study is to examine how Covid-19 has an impact on tourism in Southeast Asia, especially countries that are members of ASEAN. Analysis by region shows that the Southeast Asia region is quite influential for international tourism due to the restrictions imposed on the travel and tourism sector and several countries. This study also discusses the policies taken by the economy for countries in the Southeast Asia region and also abaout the decisions of policies taken for the country’s economy in the feature which of course have a very important impact on the development of global tourism, especially tourism in the Southeast Asian region. Even to restore tourism which had fallen drastically, countries finally opened their territorial restrictions and the country also has the challenge of returning tourist confidence, so that they can re-promote tourism in the future. There are also ASEAN countries that use several strategis such as increasing tourism information which can be done through digital platforms to help develop safe tourism corridors.